Camel Method Analysis on PT. Bank SulutGo Financial Statements for the Period 2017-2021 - Fitria Ayu Lestari Niu; Heince Ruddy Nicky Wokas; Elda Roring (Kunuz: Journal of Islamic Banking and Finance, 2022)
This study aims to analyze the level of health of the PT. Bank SulutGo in the period of 2017-2021 using the CAMEL method. The research used a quantitative descriptive method. The data display was in the form of documentation that is the data managed based on the financial statement of PT. Bank SulutGo during the period of 2017-2021. The data analysis technique using the CAMEL that is the capital adequacy ratio (CAR), asset quality (KAP), Management (NPM), Rentability (ROA and BOPO), and Liquidity (LDR) ratios. The results indicated the level of health of PT. Bank SulutGo, before the pandemic in 2017 to 2018, was predicated as healthy, with average CAMEL scores of 81% and 84%. Whereas in 2019, it decreased with a reasonably healthy predicate with a CAMEL score of 78%, which was influenced by the performance aspects of management and liquidity, which were unhealthy. However, in 2020 and 2021, during the covid-19 pandemic, it did not affect the level of health of PT. Bank SulutGo, this can be seen from the CAMEL scores of 86% and 82%, which means that predicated as healthy.